Design and Simulation of Vienna Rectifier for Harmonic Reduction in Electric Vehicle Charging Systems - Nihayatun Nafisah; Ahmad Ramadhan; Taufik Iqbal Miftaks; Bontor Panjaitan (Faculty of Engineering, Universitas Brawijaya, 2025)
The development of electric-powered transportation has increased demand for electric vehicle chargers. Most chargers used are DC chargers since energy storage in electric vehicles relies on batteries. Therefore, a rectifier is required to convert AC power sources into DC. This study aims to develop a Vienna Rectifier for electric vehicle charging systems to achieve optimal power quality. The main focus is to enhance efficiency and power quality by implementing a PID control system to reduce Total Harmonic Distortion (THD) and improve the power factor. Simulations are conducted using MATLAB Simulink with the Clarke Transformation method to optimize voltage and current control. The simulation results show that the designed Vienna Rectifier achieves a THD value below 5%, in compliance with the IEEE-519 standard, with a power factor close to 1. This demonstrates that the application of PID control in the Vienna Rectifier can improve the efficiency of electric vehicle charging while reducing the negative impact of harmonics on the power grid.